Participação racial e de gênero nas categorias gerentes, empregados especialistas, empregados qualificados e supervisores no Brasil (1992 e 2005) - Juliana Anacleto dos Santos (Ciências Sociais Unisinos)
This article focuses on the fact that white women have managed to make use of their degrees to get higher work positions with access to authority more than black women and, partly, even more than white and black men. This statement considers the significant women advance in occupations requiring higher education and exercise of authority at work, analyzing the racial contours in this configuration. Therefore there are repercussions on their income, which has changed the profile of gender categories of the Brazilian average employee.